CogniSens Athletics - Faubert, J. (2012)
CogniSens Athletics Inc. is a Montreal-based company that specializes in neurobiological science and technological applications for sports performance and assessment. The science is driven by our Chief Science Officer Dr. Jocelyn Faubert, world-leading neuro-physicist. Dr.Faubert is director of our partner the `Visual Psychophysics and Perception Laboratory` at the University of Montreal, a state of the art science research facility for which CogniSens Athletics is the commercial platform. Alongside elite in-field collaborations and an advanced sports advisory board, this unique fusion of neurophysics and sports science has been heralded with multiple awards as a leader in technology transfer. As well as accelerating the commercialization of existing neuroscience breakthroughs, CogniSens Athletics is set to transform a continous flow of perceptual-cognitive technologies into real sports technologies to push forward the boundaries of athletic conditioning and assessment. CogniSens Athletics continues to develop patentable sport-specific cognitive training applications, validated through collaborations with professional teams in each major sport. Perceptual-cognitive abilities utilize many tiers of high level mental resources that are pushed to their maximum through the extreme mental demands of team sports. These abilities are heavily influenced by the brain's remarkable neuroplasticity - the ability to self-reorganize to increase perfomance based on functional demands. Through an extensive team of scientists and sensory technologies, Dr.Faubert directs numerous research projects at the frontiers of sports neurophysics knowledge. These focus on performance conditioning and neurobiological assessments. Some project synopses are presented here as examples of CogniSens Athletics research and development under Dr.Faubert. With solid partners in NHL, NFL, EPL, NCAA, FFR, and Olympic training centers, CogniSens Athletics also strives to provide an intermediary science role through a knowledge sharing approach between leaders in separate sports. A fluid osmosis of ideas has spawned the R&D of many unique applications grounded in elite performance needs.